Managerial Economics : a Strategic Approach. - Waschik, Robert (Taylor & Francis, 2010)
Offers an introduction to the key pillars of game theory into managerial decision-making. Taking an international perspective, this book shows developments in economics such as behavioural economics and auction theory as well as how these can be applied in the workplace.